ANALYSIS ON WATER POTENTIAL AND REQUIREMENT FOR RECOMMENDING SUPPLEMENTARY IRRIGATION ON UPLAND SUGARCANE - IRIANTO, GATOT; SURMAINI, E. (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2002)
Sugarcane planted in dry season (April to September) in Lampung usually experiences water deficit especially during initial and vegetative phases. Compared with other phases, water deficit in those periods decreases yield badly. To minimize water stress and estimate irrigation need, the research was conducted in two steps as follows: (1) analysis of water resources potential using hydrological water balance, (2) estimating water balance within rooting zone and yield loss potential using ETR/ETM ratio of FAO for recommending supplementary irrigation. The results showed that the sugarcane planted in April, May, and June suffered with water supply of135, 151, and 106 m3 in June, July, and August, respectively. Water deficit caused ETR/ETM value fell below minimum requirement (0.65) with yield loss between 16-45%. Based on the water requirement, water holding capacity, and minimum requirement of ETR/ETM, recommended irrigation during critical phases was 20 mm weekly. The recommendation was able to minimize yield loss from 16-45% to become 4-21%. Based onwater resources identifications within and the adjacent areas, irrigation requirement could be provided sufficiently if number, distribution, capacity, and mechanism of run off harvesting in cascade channel reservoir are optimum.